Food insecurity coping strategies in conflict-affected Libya. Issue 3 (2nd April 2020) - Swesi, Rashd; El-Anis, Imad; Islam, Md Mofakkarul
ABSTRACT: This article explored whether there were lessons to be learnt for food security assessment and interventions by studying household food insecurity coping strategies in conflict contexts. Data were collected using 55 in-depth interviews during 2016–2017 from three regions in Libya – a country affected by protracted conflicts since 2011. Thematic analyses revealed eight major categories of coping strategies, some of which resembled those reported in the global literature. However, some strategies, both negative and positive, were unique to the conflict context. The implications of the findings for food security assessment and interventions in areas of protracted conflicts are discussed.